1988
DOI: 10.1111/j.1476-5381.1988.tb11655.x
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine receptor‐mediated contraction and relaxation of guinea‐pig isolated tracheal smooth muscle: effects of adenosine antagonists

Abstract: 1 The effects of several adenosine analogues and antagonists on guinea-pig isolated trachea have been examined. 2 5'-N-ethylcarboxamidoadenosine (NECA), 5'-N-methylcarboxamidoadenosine (MECA) and adenosine (in the presence and absence of dipyridamole) elicited concentration-dependent tracheal relaxation.3 The R(-)-and S( +)-enantiomers of N642-phenylisopropyl)adenosine (R-PIA and S-PIA respectively), N6-cyclohexyladenosine (CHA) and 2-chloroadenosine (CADO) caused contractions at low concentrations (0.05-2.0 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
1

Year Published

1991
1991
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 29 publications
3
47
1
Order By: Relevance
“…Since the cyclooxygenase inhibitor in domethacin completely inhibited R-PIA-in duced contraction, it is suggested that the con tractile response elicited by R-PIA is mediated by cyclooxygenase metabolites, such as con strictor PGs. Similar results have been re ported by Farmer et al (18) and Caparrotta et al (19). Since NZ-107 (1 ,uM) significantly in hibited the contraction induced by PGF2a, it is suggested that NZ-107 reduces R-PIA-induced contraction by inhibiting the contraction in duced by endogenously released PGF2a.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Since the cyclooxygenase inhibitor in domethacin completely inhibited R-PIA-in duced contraction, it is suggested that the con tractile response elicited by R-PIA is mediated by cyclooxygenase metabolites, such as con strictor PGs. Similar results have been re ported by Farmer et al (18) and Caparrotta et al (19). Since NZ-107 (1 ,uM) significantly in hibited the contraction induced by PGF2a, it is suggested that NZ-107 reduces R-PIA-induced contraction by inhibiting the contraction in duced by endogenously released PGF2a.…”
Section: Discussionsupporting
confidence: 77%
“…The ineffectiveness of AP on forskolin-induced relaxation may be related to the lack of the increase in cAMP at 30 uM. Farmer (18) reported that a xanthine deriva tive, enprofylline, which is not an adenosine antagonist but a potent PDE inhibitor (20), had little effect on R-PIA-induced contraction in the guinea pig trachea. Thus it is unlikely that the inhibitory effect of NZ-107 on Al mediated contraction results from PDE inhibi tion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in several tissues, such as the guinea-pig trachea and aorta, the presence of both subclasses of P1-purinoceptor has been reported, in each case the Al receptor mediates contraction while only the A2 mediates relaxation (Farmer et al, 1988;Stoggall & Shaw, 1990). For two receptor subtypes to mediate the same response in one tissue preparation is unusual, and it is not at all clear why such an apparently redundant system should have evolved.…”
Section: Discussionmentioning
confidence: 98%
“…Previous functional studies on the rat duodenum showed that this tissue contained a mixture of Al and A2b receptors both mediating relaxation (Nicholls et al, 1992 ceptor mediated contraction while only the A2 receptor mediated relaxation (Farmer et al, 1988;Stoggall & Shaw, 1990;Bailey & Hourani, 1990; Pharmacology (1996) 117,[170][171][172][173][174] Methods Male Wistar rats, University of Surrey strain, (200-250 g) were killed by cervical dislocation. The duodenum was dissected out by cutting at the base of the pyloris and 1.5 cm from this point, cleared of any connective tissue and placed over a fine bore (diameter: 5 mm) pipette and a longitudinal cut made.…”
Section: Introductionmentioning
confidence: 99%